Sensory Experiences and Children With Severe Disabilities: Impacts on Learning - Agostine, Susan; Erickson, Karen; D’Ardenne, Charna (Frontiers in Psychology, 2022)
The human sensory system is continuously engaged in experiencing and interpreting every interaction with other living beings, objects, and the environment. The purpose of this article is to describe the impact limited opportunities for rich sensory experiences have on students with severe disabilities in two middle school classrooms situated in a public separate school in the southeastern USA. The study employed a postcritical ethnographic approach and grounded theory thematic analysis of fieldnotes gathered over a two-year period. Three major themes supported by the data are presented and discussed in depth. They are: (a) students are afforded limited sensory rich experiences, (b) everyday routines make students passive recipients to school, and (c) instructional approaches result in little interaction with extended periods of waiting. The implications of the findings for improved sensory experiences and possible future directions are described.